Ionizing radiation technologies to increase the extraction of bioactive compounds from agro-industrial residues: a review - Cabo Verde, Sandra (2018)
Due to the growing demand in society for healthier foods, scientific communities are searching and developing new ingredients. In this context, agro-industrial residues, which can have a negative impact on the environment, represent a natural source for bioactive compounds and their recovery can contribute to economic and environmental sustainability. Ionizing radiation is a clean and eco-friendly technology that can be used to improve the extraction of bioactive compounds. The aim of this review, after presenting general aspects about bioactive compounds in agro-industrial residues and radiation technologies, is to focus on the effects of ionizing radiation on the extraction of bioactive compounds from these residues and related bioactive properties. Irradiated residues were demonstrated to have enhanced bioactive characteristics that turn the prepared extracts suitable for applications in food industry, resulting in high-added-value products as well as reducing adverse impacts on the environment.